Cost Evaluation of the Ontario Virtual Urgent Care Pilot Program: Population-Based, Matched Cohort Study - Jean-Eric Tarride; Justin N Hall; Shawn Mondoux; Katie N Dainty; Joy McCarron; J Michael Paterson; Lesley Plumptre; Emily Borgundvaag; Howard Ovens; Shelley L McLeod (JMIR Publications, 2024)
BackgroundIn 2020, the Ministry of Health (MoH) in Ontario, Canada, introduced a virtual urgent care (VUC) pilot program to provide alternative access to urgent care services and reduce the need for in-person emergency department (ED) visits for patients with low acuity health concerns. ObjectiveThis study aims to compare the 30-day costs associated with VUC and in-person ED encounters from an MoH perspective. MethodsUsing administrative data from Ontario (the most populous province of Canada), a population-based, matched cohort study of Ontarians who used VUC services from December 2020 to September 2021 was conducted. As it was expected that VUC and in-person ED users would be different, two cohorts of VUC users were defined: (1) those who were promptly referred to an ED by a VUC provider and subsequently presented to an ED within 72 hours (these patients were matched to in-person ED users with any discharge disposition) and (2) those seen by a VUC provider with no referral to an in-person ED (these patients were matched to patients who presented in-person to the ED and were discharged home by the ED physician). Bootstrap techniques were used to compare the 30-day mean costs of VUC (operational costs to set up the VUC program plus health care expenditures) versus in-person ED care (health care expenditures) from an MoH perspective. All costs are expressed in Canadian dollars (a currency exchange rate of CAD $1=US $0.76 is applicable). ResultsWe matched 2129 patients who presented to an ED within 72 hours of VUC referral and 14,179 patients seen by a VUC provider without a referral to an ED. Our matched populations represented 99% (2129/2150) of eligible VUC patients referred to the ED by their VUC provider and 98% (14,179/14,498) of eligible VUC patients not referred to the ED by their VUC provider. Compared to matched in-person ED patients, 30-day costs per patient were significantly higher for the cohort of VUC patients who presented to an ED within 72 hours of VUC referral ($2805 vs $2299; difference of $506, 95% CI $139-$885) and significantly lower for the VUC cohort of patients who did not require ED referral ($907 vs $1270; difference of $362, 95% CI 284-$446). Overall, the absolute 30-day costs associated with the 2 VUC cohorts were $18.9 million (ie, $6.0 million + $12.9 million) versus $22.9 million ($4.9 million + $18.0 million) for the 2 in-person ED cohorts. ConclusionsThis costing evaluation supports the use of VUC as most complaints were addressed without referral to ED. Future research should evaluate targeted applications of VUC (eg, VUC models led by nurse practitioners or physician assistants with support from ED physicians) to inform future resource allocation and policy decisions.